2017
DOI: 10.26717/bjstr.2017.01.000591
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of Discussion Concerning Sexual and Reproductive Health Issues Among Adolescents and Parents, Hawassa, SNNPR, Ethiopia

Abstract: Background: Adolescence is a period of high developmental changes in physical, mental and social conditions. In this period the adolescent youth fails to control their emotions, listen to parents' advice and begins to indulge them in unhealthy behavioral activities. In general, the age group from 10 to 19 years is classified as adolescent. Many adolescents often lack strong and stable relationships with their parents to openly discuss about reproductive health concerns. Similarly, about 55.7% of the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…This finding indicated that parents are not open to their children in discussion related to SRH which leads young people to feel embraced in discussion of sexual related issues. The finding of this study is consistent with studies conducted in Hawassa, Ethiopia [23] and Johannesburg, South Africa [21]. In the same manner, family size where the study participants live was found to be significantly associated with discussion on SRH issues.…”
Section: Discussionsupporting
confidence: 91%
“…This finding indicated that parents are not open to their children in discussion related to SRH which leads young people to feel embraced in discussion of sexual related issues. The finding of this study is consistent with studies conducted in Hawassa, Ethiopia [23] and Johannesburg, South Africa [21]. In the same manner, family size where the study participants live was found to be significantly associated with discussion on SRH issues.…”
Section: Discussionsupporting
confidence: 91%
“…(21,24,31,32), But this nding higher than studies conducted in Awabel (25.3%) and Mizan (28.9%) this might due to time variation and socio demographic difference like in Awabel the magnitude of urban population was 23.9% which is lower than the study area and in Mizan about 57.3% of populations were unable to read and write which is higher than the study area (33,34). This nding is lower than stuies conducted in Yirgalem (59.1%), Debre-markos (36.9%), Dire-dawa (37%), Hawassa (61%), South Africa (57%), Ghana (72.8%) and Mynamar (62%) this might due to study area difference (these studies conducted at institution but this study was community based), lower illiteracy rate (Debre-markos 20.5%, Yirgalem 7.4%, and Dire-dawa 20.5% and Myanmar 6.3%) and more urbanized (Mekelle 84.9%, Hawassa 73.2%) (4,5,7,20,23,35,36).…”
Section: Resultsmentioning
confidence: 92%
“…Studies conducted in Ethiopia focus on from the adolescent perspective (there are evidences which showed that when adolescent asks about communication most of them are said yes, but when the parent asks about communication the result is different this results wrongly determination of magnitude of parent-adolescent communication), conducted in urban residence and institution based (4,21,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Factors related to adolescent-parent communication have been documented to be (for the adolescent): experience of sexual pleasure, following social media, using a condom, talking to friends about sex-related issues, and feeling ashamed of talking about sexual issue. 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 Factors related to adolescent-parent communication have been documented to be (for the adolescent): experience of sexual pleasure, following social media, using a condom, talking to friends about sex-related issues, and feeling ashamed of talking about sexual issue. 7 Measuring both mothers' and daughters' perception of communication on sexual behaviors can provide insights into family characteristics that may be important targets for sexual health promotion programs for adolescent girls. 8 Almost all studies conducted in Ethiopia focused on adolescent-parent communication in general, 5,[9][10][11][12][13][14][15][16] while this study addressed daughter-mother communication, which is critical in addressing gender-specific concerns problems like unwanted pregnancy and abortion.…”
Section: Introductionmentioning
confidence: 99%